The Role of Histone Acetyltransferases in Normal and Malignant Hematopoiesis - Sun, Xiao-Jian; Man, Na; Tan, Yurong; Nimer, Stephen D.; Wang, Lan (Frontiers in Oncology, 2015)
Histone or non-histone protein acetylation plays important roles in all kinds of cellular events, including the normal and abnormal development of blood cells, through changing the epigenetic status of chromatin and regulating non-histone protein’s function. Histone acetyltransferases (HATs), which are the enzymes responsible for the histone or non-histone protein acetylation, contain p300/CBP, MYST and GNAT family etc. HATs are not only the protein modifiers and epigenetic factors, but also the critical regulators of cell development and cancerogenesis. Here we will review the function of HATs such as p300/CBP, Tip60, MOZ/MORF and GCN5/PCAF in the normal hematopoiesis and the pathogenesis of hematological malignancies. The inhibitors that have been developed to target HATs will also be reviewed here. Understanding the roles of HATs in normal/malignant hematopoiesis and the underlying mechanism will provide the potential therapeutic targets for the hematological malignancies.